Performance Analysis of On-Grid Solar Power Plant under Various Irradiation and Load Condition - Asri, Andarini; L, Ruslan; Annisa, Annisa; Farid, Andi Fahrul (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2024)
This research aims to analyze the effect of irradiation and load variations on the performance of the 1 kWp on-grid solar power plant at Ujung Pandang State Polytechnic. The research was conducted for 7 days with component testing on May 8, 2024, irradiation variation testing on May 15-17 and June 5-6, 2024, and load variation testing on June 8, 2024. MATLAB GUI was used to theoretically calculate power, PV and GTI efficiency, Yf, Yr, PR, apparent power, and load reactive power. In addition, the MATLAB GUI also displays graphs of the effect of irradiation variations on the performance of solar power plants. PSIM simulation was used to compare the PV power generated with the same irradiation and temperature. The results show that irradiation greatly affects the performance of the solar power plant, where increasing irradiation increases the output power, PV and GTI efficiency, and export power to the grid, which results in an increase in Yf, Yr, and PR. PSIM simulations support these findings by showing a positive correlation between irradiation and PV output power. Load variation also affects the Pf value, where resistive (R) loads have the best Pf (1), while inductive-capacitive (LC) loads have the worst Pf (0.37) due to the high reactive power drawn. Thus, variations in load type affect power consumption and system performance.